The Application of Digitalization Skills of Business Actors Mediates The Impact of Business on MSME Performance - Rully Nurliah; Syahdilla Azzahra R; Elsa Wafiq Azizah; Anna Suzana; Dharliana Hardjowikarto (Journal Research of Social Science, Economics, and Management, 2024)
The application of digitalization skills to social media can affect the impact of business on MSME performance. The purpose of this study is to test and find out digital technology in the application of digitalization skills can mediate the impact of business on MSME performance. This study uses a quantitative approach with the design of questionnaire methods and explanatory research, with purposive sampling on the types of products marketed, MSMEs that make sales using social media and e-commerce, and MSMEs that have conducted entrepreneurship training, a sample of 268 MSMEs with a response rate of 50 MSMEs. The analysis used is SmartPLS. The results of the analysis show that the application of digitalization skills partially mediates the impact of business on MSME performance. Digital technology is an intermediary variable that is able to compete in the global market, because MSME players can do online marketing so that product sales can increase and digital technology is able to process products more efficiently by utilizing technology, and can distribute products more effectively. Business impact using the strategies applied, namely communication with media selection, competitive advantage refers to business competition, and innovation for product development. Financial performance has increased sales, non-financial performance has experienced accuracy in sales targets and develops business through the potential of human resources owned.